2020
DOI: 10.1071/fp19362
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the size of photosystem II light harvesting antenna represents a universal mechanism of higher plant acclimation to stress conditions

Abstract: We investigated acclimatory responses of Arabidopsis plants to drought and salinity conditions before the appearance of obvious signs of damage caused by these factors. We detected changes indicating an increase in the reduction level of the chloroplast plastoquinone pool (PQ pool) 5–7 days after introduction of the stress factors. After 10–14 days, a decrease in the size of PSII light harvesting antenna was observed in plants under conditions of drought and salinity. This was confirmed by a decrease in conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 76 publications
0
8
0
Order By: Relevance
“…The redox state of the PQ pool regulates the expression of chloroplast genes, including psaAB and psbA encoding core peptides of photosystems, and rbcL encoding a large subunit of rubisco. It is also known to regulate expression of nuclear genes: i.e., lhcb encoding antenna complexes, plastocyanin, ferredoxin, nitrate reductase, superoxide dismutase, ascorbate peroxidase and some enzymes of the carotenoid biosynthetic pathway [ 9 , 42 , 154 , 155 , 156 , 157 ]. The above-mentioned STN7 kinase, as well as chloroplast sensor kinase (CSK) participate in PQ-dependent redox signaling, leading to changes in the expression of plastid genes during acclimation to long-term light-quality shifts [ 156 ].…”
Section: Role Of Ros and Prenyllipid Antioxidants In Cellular Signmentioning
confidence: 99%
“…The redox state of the PQ pool regulates the expression of chloroplast genes, including psaAB and psbA encoding core peptides of photosystems, and rbcL encoding a large subunit of rubisco. It is also known to regulate expression of nuclear genes: i.e., lhcb encoding antenna complexes, plastocyanin, ferredoxin, nitrate reductase, superoxide dismutase, ascorbate peroxidase and some enzymes of the carotenoid biosynthetic pathway [ 9 , 42 , 154 , 155 , 156 , 157 ]. The above-mentioned STN7 kinase, as well as chloroplast sensor kinase (CSK) participate in PQ-dependent redox signaling, leading to changes in the expression of plastid genes during acclimation to long-term light-quality shifts [ 156 ].…”
Section: Role Of Ros and Prenyllipid Antioxidants In Cellular Signmentioning
confidence: 99%
“…The antenna system mainly responsible for light harvest and electron transfer, but there are sensitive to stresses factor, especially drought environment [37]. Therefore, we found numerous chlorophyll a-b binding elements (CP24, CP25, CP29, CP30 and other members), PSI reaction center subunits (PsaD, PsaF, PsaE, PsaG, PsaH, PsaK, PsaL and PsaN) and PSⅡ reaction center subunits (PsbY, PsbW, PsbS and PsbR) were significantly decreased.…”
Section: Responses Of Photosynthetic System Involved In Drought Stressmentioning
confidence: 86%
“…This result may be related to post-transcriptional modification of genes ( Guerra et al, 2015 ), which suggests that chlorophyll synthesis in the two phenotypes may be similarly regulated at the protein level. PSII and PSI are mainly responsible for light energy harvesting and transfer, and the stability of PSII and PSI systems is closely related to photosynthetic efficiency ( Borisova-Mubarakshina et al, 2020 ). Studies have suggested that a decrease in PSII and PSI system subunit-encoding genes can inhibit the photoreaction process ( Guo et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%